Better functional outcome after femoral neck fracture for patients treated with total hip arthroplasty compared to internal fixation? - Frondelius, Eemil (My University, 2023)
Background: Internal fixation (IF) and total hip arthroplasty (THA) are both used as treatment in femoral neck fractures (FNF). Decision on surgical method is made on an individual level, depending on patients’ functional demands and fracture type. The goal of this study was to evaluate whether THA provides better functional outcome compared to IF when evaluated by Oxford Hip Score (OHS). Patients and Methods: A total of 132 FNF patients were included. Thirty-six (27%) of the patients underwent IF and 96 (73%) THA. Mean age was 68 (SD 9) years and 86 (65%) were female. The results were analyzed using a linear mixed-effects model. Results: At one year the mean difference in OHS scores between patients treated with THA and IF was 7.5 points (95% CI 3.6-11.4, p=0.0003). When those patients who had revision surgery during the follow up time were removed from the analysis the difference decreased but was still statistically significant with a mean difference of 4.4 (95% CI 0.7-8.0, p=0.02). The contrast between the two groups was statistically significant for the first 850 days. Five (14%) patients in the IF group and one (1%) patient in the THA group underwent a reoperation. When the revised patients were removed from the sample the difference is mitigated but still statistically significant with a mean difference of 4.35 points (95% CI 0.65-8.05, p=0.02). Conclusions: The patients treated with THA had a better functional outcome compared to IF at the one-year follow-up.